1986
DOI: 10.1073/pnas.83.18.6776
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequence of a cDNA coding for the human beta-migrating endothelial-cell-type plasminogen activator inhibitor.

Abstract: A Xgtll expression library containing cDNA inserts prepared from human placental mRNA was screened immunologically using an antibody probe developed against the ,8-migrating plasminogen activator inhibitor (p-PAI) purified from cultured bovine aortic endothelial cells. Thirty-four positive clones were isolated after screening 7 x i0-phages. Three clones (X1.2, X3, and X9.2) were randomly picked and further characterized. These contained inserts 1.9, 3.0, and 1.9 kilobases (kb) long, respectively. Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(181 citation statements)
references
References 47 publications
7
171
0
3
Order By: Relevance
“…This is in agreement with the known amino acid sequence of PAl: Val-His-His-ProPro-Ser-Tyr-Val- [4] and that of vitronectin: AspGln-Glu-Ser-Cys-Lys-Gly-Arg- [12].…”
Section: Purification Of the Pal-binding Proteinsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with the known amino acid sequence of PAl: Val-His-His-ProPro-Ser-Tyr-Val- [4] and that of vitronectin: AspGln-Glu-Ser-Cys-Lys-Gly-Arg- [12].…”
Section: Purification Of the Pal-binding Proteinsupporting
confidence: 91%
“…In contrast, functionally inactive or so called 'latent' PAl filters as a 50 kDa compound [2,3], in agreement with its suggested primary structure [4]. Recently we presented evidence that the deviating gel filtration behaviour of functionally active PAI in the presence of plasma/serum is due to the existence of a discrete PAl-binding protein in plasma/serum [3].…”
Section: Introductionsupporting
confidence: 76%
“…Northern blot analysis indicated that, in a dose-dependent manner, TNF increased PAI-2 mRNA, as well as the 3.4-and 2 .4-bp species (17) of PAI-1 mRNA, while at the same time suppressing t-PA mRNA (Fig . 1) .…”
Section: Resultsmentioning
confidence: 99%
“…A 2.9-kilobase (kb) PAI-1 cDNA probe described previously 24 was used in hybridization analysis and was kindly provided by Tor Ny, University of Umea, Sweden. The Hindlll polymorphism was that first described by Klinger et al 15 DNA was prepared from blood using standard techniques.…”
Section: Dna Analysismentioning
confidence: 99%